The system effect and group benefit equity of long-term care insurance from the perspective of short-term policy pilot - He, Wei; Liu, Huan (Frontiers in Public Health, 2025)
MethodsThis study focuses on the long-term care insurance (LTCI) policy pilot, using the CHARLS database to continuously track survey data. It constructs a difference in-difference model based on city, time, coverage, and beneficiaries to accurately identify policy coverage and empirically examine the institutional effect of the long-term care insurance policy pilot and the fairness of group benefits.ResultsThe results indicate that the policy pilot has a significant positive impact on the overall medical consumption of disabled older adults, with impacts on monthly outpatient consumption, annual hospitalization consumption, annual hospitalization times, and last hospitalization days of 0.7064, 0.4142, 0.0887, and 1.5607, respectively. In addition, the LTCI policy pilot significantly and positively affected disability-related health indicators such as individual self-assessment health, ADL disability, and the number of serious diseases, with effect sizes of 0.8677, 1.0854, and 0.6668, respectively.DiscussionThe results regarding group benefit equity show that the LTCI policy pilot can improve the equity of medical consumption and disability-related health among groups; however, over time, it may exacerbate the inequality of medical consumption and disability-related health among disabled older adults in the treatment group. Based on this, the study finds that the LTCI policy pilot has effects on medical consumption and disability-related health for disabled older adults, primarily driven by the moral hazard associated with the assessed individuals obtaining LTCI treatment due to the short-term policy pilot.